2016
DOI: 10.1007/s40195-016-0437-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characteristics in Seawater for Cold Thermal Spray-Coated Al–Mg Alloy Layer

Abstract: For corrosion protection of carbon steel in a marine environment, cold arc thermal spray coating was applied to the surface with Al and Al-Mg alloy wires. The surface hardness of Al and Al-Mg thermal spray coatings increased with Mg content. And the various electrochemical experiments were carried out to evaluate corrosion damage characteristics of the thermal spray coating layers. The Al and Al-Mg thermal spray coating layers presented negative potentials compared to carbon steel in corrosion potential measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This result suggests that 1 M NaH2PO4 with 0.1 Ca(NO3)2 i.e., SPCN3, is not beneficial for corrosion resistance at a longer duration of exposure in 3.5 wt.% NaCl solution but at a shorter duration i.e., up to 11 days it has shown highest impedance ( Figure 5) owing to the greater filling ability of defects. It is reported that if the coating shows Ecorr at −0.870 V vs. Ag/AgCl then such type of coating is considered as a sacrificial coating [68]. Since, in the present study, AC, SPCN1, and SPCN2 exhibit more than −0.870 V vs. Ag/AgCl, it indicates that these coatings are providing sacrificial protection to the steel even after 89 days of exposure in 3.5 wt.% NaCl solution.…”
Section: Potentiodynamic Polarization Resultsmentioning
confidence: 48%
“…This result suggests that 1 M NaH2PO4 with 0.1 Ca(NO3)2 i.e., SPCN3, is not beneficial for corrosion resistance at a longer duration of exposure in 3.5 wt.% NaCl solution but at a shorter duration i.e., up to 11 days it has shown highest impedance ( Figure 5) owing to the greater filling ability of defects. It is reported that if the coating shows Ecorr at −0.870 V vs. Ag/AgCl then such type of coating is considered as a sacrificial coating [68]. Since, in the present study, AC, SPCN1, and SPCN2 exhibit more than −0.870 V vs. Ag/AgCl, it indicates that these coatings are providing sacrificial protection to the steel even after 89 days of exposure in 3.5 wt.% NaCl solution.…”
Section: Potentiodynamic Polarization Resultsmentioning
confidence: 48%
“…Moreover, the Al coating exposed to 3.5 wt. % NaCl solution provides cathodic protection where its corrosion potential (Ecorr) is greater than -0.870 V vs Ag/AgCl (Park and Kim, 2016) while in SAE J2334 solution, it is gradually corroded.…”
Section: Deposition Of Al Coating and Characteristicsmentioning
confidence: 99%
“…There are many published studies of the Al-Mg alloy coatings in recent years. [1][2][3][4][5][6][7][8] he corrosion resistance in 3.5 wt.% NaCl solution of flamesprayed Al-5Mg alloy coating has better than that of Al-2.5Mg coating. [1] The Al-Mg coatings with high Mg content have lower surface strength and higher resistance to the development of cracks than the coatings with low Mg content.…”
Section: Introductionmentioning
confidence: 99%
“…[2] The corrosion resistance of the cold sprayed Al-Mg coating is higher than that of the cold sprayed pure Al coating in the actual marine environment. [3][4][5] The service lifetime of the Al-Mg alloy coating can be improved by using the organic coating, preventing contact with the corrosion solution. [6] In the authors' previous study, the spray mode consisting of spray current, pneumatic pressure, and stand-off distance were optimized using the Taguchi method.…”
Section: Introductionmentioning
confidence: 99%